Analysis of the Effect of Bottom Blade Inclination Angle Variations on Torque in Vortex Turbines Using Computational Fluid Dynamics (CFD) - Badri Kurniawan; Randi Purnama Putra; Yolli Fernanda; Fitrah Qalbina (Unversitas Negeri Padang, 2025)
The development of renewable energy in Indonesia is a strategic effort to meet increasing energy demands while reducing dependence on fossil fuels. One promising approach is utilizing river flow for micro-hydro power generation, particularly with vortex turbines that operate efficiently under low head and discharge conditions. This study aims to analyze the effect of varying bottom blade inclination angles on the torque generated by a vortex turbine using Computational Fluid Dynamics (CFD) simulations. The research employed ANSYS Fluent with a k-? SST turbulence model and used a three-dimensional numerical method to evaluate three inclination angles: 22.5°, 32°, and 42°. The results show that blade inclination significantly influences torque values, with the 22.5° angle producing the highest torque of 10.95 Nm, followed by 32° at 10.79 Nm, and 42° at 10.58 Nm. These findings indicate that optimizing blade inclination improves turbine performance, contributing to the development of efficient micro-hydro systems for renewable energy applications.